2013
DOI: 10.1038/bjc.2013.592
|View full text |Cite
|
Sign up to set email alerts
|

A reanalysis of cancer mortality in Canadian nuclear workers (1956–1994) based on revised exposure and cohort data

Abstract: Background:A 15-country study of nuclear workers reported significantly increased radiation-related risks of all cancers excluding leukaemia, with Canadian data a major factor behind the pooled results. We analysed mortality (1956–1994) in the updated Canadian cohort and provided revised risk estimates.Methods:Employment records were searched to verify and revise exposure data and to restore missing socioeconomic status. Excess relative risks per sievert (ERR/Sv) of recorded radiation dose and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 24 publications
1
53
2
Order By: Relevance
“…A statistically significant increase in cancer mortality was originally found in this group, but subsequent analyses excluding data from Canada (which were determined to be flawed) eliminated the statistical significance of the study. 30,31 A high-quality study 32 from the United Kingdom focusing on occupational exposures did report a small but statistically significant increase in cancer risk, albeit at dose levels much higher (200-500 mSv) than the dose levels typically associated with diagnostic imaging (<1-25 mSv).…”
Section: How Much Radiation Is Dangerous?mentioning
confidence: 99%
“…A statistically significant increase in cancer mortality was originally found in this group, but subsequent analyses excluding data from Canada (which were determined to be flawed) eliminated the statistical significance of the study. 30,31 A high-quality study 32 from the United Kingdom focusing on occupational exposures did report a small but statistically significant increase in cancer risk, albeit at dose levels much higher (200-500 mSv) than the dose levels typically associated with diagnostic imaging (<1-25 mSv).…”
Section: How Much Radiation Is Dangerous?mentioning
confidence: 99%
“…9 Without the Canadian data, the 15-country study would not show an increased risk of cancer from low-dose radiation. 10 A third data set Brenner used was the Oxford study 11 of childhood cancers, a case-control study that showed increased risk of childhood cancers following prenatal radiation. Major deficiencies have been identified in this study, and publications have raised doubts about a causal link between prenatal radiation and childhood leukaemias observed in such studies, since cohort studies involving much higher radiation doses in atomic bomb survivors have failed to show the increased risk of childhood leukaemias.…”
mentioning
confidence: 99%
“…The NDR has also been an important source of data for several epidemiological investigations of exposure and disease among different occupational groups in Canada. [12][13][14] The Ontario Asbestos Workers Registry, also a mandatory registry, has similar goals in terms of prospectively monitoring exposure and notifying workers who reach a particular duration of exposure, but has not to date been used for any surveillance or epidemiological investigations, though these activities could be supported. 15 Though none of the Canadian registries did so, exposure registries can also be used as a basis for medical screening in individuals.…”
Section: Discussionmentioning
confidence: 99%